2010
DOI: 10.1259/dmfr/16270943
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of clinical and radiographic signs of osteoarthrosis of the temporomandibular joint in an older persons community

Abstract: Objectives: The aim was to assess the prevalence of osteoarthrosis (OA) in the temporomandibular joint (TMJ) in a sample of older people by use of contrast agentenhanced MRI. Methods: 30 patients (73-75 years old) were drawn from a representative sample and were examined clinically. The shape of the condyle was assessed using gadolinium-enhanced MR images, which were evaluated by two independent raters. Statistical assessment was performed by using descriptive statistics, the x 2 test and kappa statistics. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 14 publications
2
52
0
7
Order By: Relevance
“…21 Several studies reveal that there is a poor correlation between condylar changes (as observed on CBCT or magnetic resonance imaging), pain and other clinical signs and symptoms of TMJ osteoarthitis. 22,23 In standard practice, orthodontic and orthognathic treatment can be started after craniofacial growth has ceased, which accounts for the mean age in the Class II and Class III groups, with which the Class I subjects were matched. The relatively young age of the patients is a factor that must be taken into consideration when analysing and comparing the results.…”
Section: Discussionmentioning
confidence: 99%
“…21 Several studies reveal that there is a poor correlation between condylar changes (as observed on CBCT or magnetic resonance imaging), pain and other clinical signs and symptoms of TMJ osteoarthitis. 22,23 In standard practice, orthodontic and orthognathic treatment can be started after craniofacial growth has ceased, which accounts for the mean age in the Class II and Class III groups, with which the Class I subjects were matched. The relatively young age of the patients is a factor that must be taken into consideration when analysing and comparing the results.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption that OA might be the primary cause of pain cannot be supported by our study, in line with previous studies on the relationship between TMJ pain and anatomic changes in the TMJ 33 and on OA in elderly people, in whom joints exhibiting OA were largely asymptomatic. 34 In the absence of abnormalities on MRI, such as anterior disc displacement, joint effusion, condylar fractures or neoplasms, TMJ pain can be connected with an altered disc position in the MRI oblique coronal plane. In painful TMJs, the disc appears to be reduced in its transverse dimensions and less medially located than in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that there are a finite number of mandibular condylar cartilage progenitor cells; once the cells are depleted, repair remodeling and growth diminish in capacity. Like other joints, the TMJ degenerates with age 4, 5 . However, women between the ages of 44–55 years are most likely to seek treatment 6, 7 , suggesting a role for estrogen in the disease process.…”
Section: Introductionmentioning
confidence: 99%